PRPOPAGANDA AMERIKA SERIKAT TERHADAP TIONGKOK MELALUI FILM CONTAGION TAHUN 2011 - Redha Alfian; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research describes the effort of United States of America in doing Propaganda toChina through Contagion 2011. The rise of China become a security dilemma for United States.Contagion tells a virus disaster spread all around the world. China is actually the first countryfound the MEV-1, a fiction Virus created By Soderbergh the director of Contagion. China also acountry that the mostly shown up after United State. The purpose of this study is to find outweather America do such propaganda to China or not.This research is using descriptive andlibrary research methods.The data and information obtained from books, journals and websites.This research uses Constructivism perspective and propaganda Theory. The result of thisresearch shows that United state of America try to defend the hegemonic power from the rise ofChina. By using a movie, United state run a kind of soft diplomacy. Even China didn’t give asignificant respond of this movie. But United State was trying create an international publicopinion about terror and Chinese since the movie was released in 9 September 2011, the day ofWorld Trade Center tragedy. The movie also pictures how an epidemics spread out ofinternational world.Keyword : United State of America, Propaganda, Virus, China, Terror